Microstructure and elevated temperature mechanical properties of bimetal part fabricated by laser powder bed fusion of AlSi10Mg on rolled AA6061-T651 - ZainElabdeen, Ibrahim H.; Umer, Rehan; Cantwell, Wesley J.; Weston, James; Khan, Kamran A. (Materials & design, 2025)
[Display omitted] •A bimetallic structure was successfully fabricated by printing aluminum–silicon alloy onto rolled aluminum alloy using laser powder bed fusion.•The interface between the two alloys exhibited strong metallurgical bonding with no observable defects.•Mechanical testing at elevated temperatures confirmed that fracture consistently occurred away from the interface, validating its integrity.•Post-processing heat treatments enhanced ductility but led to reduced strength and hardness of the bimetallic structure. This study employed laser powder bed fusion (LPBF) to deposit AlSi10Mg onto rolled AA6061-T651, aiming to evaluate the microstructure and mechanical performance of the resulting bimetallic structure. The microstructure was characterized using scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), electron backscatter diffraction (EBSD), and micro-computed tomography (µ-CT). Mechanical properties were assessed via nanoindentation and uniaxial tensile testing at room temperature and elevated temperatures up to 250 °C. The bimetal underwent three heat-treatment cycles: stress relief (SR), solution heat treatment followed by direct aging (T6), and a combined SR and T6 treatment. A robust, defect-free interface (∼70 µm thick) was observed, driven by Marangoni convection, resulting in intermixing. The mechanical response of the bimetal was governed by the weaker alloy at all temperatures. At room temperature and 100 °C, fractures occurred on the AA6061 side, whereas at higher temperatures, failure shifted to the AlSi10Mg side due to its greater thermal softening. Heat treatments improved ductility but reduced strength and nanohardness. Overall, these findings demonstrate LPBF’s effectiveness in producing strong metallurgical bonds between dissimilar aluminum alloys, offering promising solutions for structural repair and multi-material designs in applications demanding reliability at both ambient and elevated temperatures.